Fermented Rosa Roxburghii Tratt Juice Alleviates High-Fat Diet-Induced Hyperlipidemia in Rats by Modulating Gut Microbiota and Metabolites - Ji, Jiacheng; Zhang, Shuo; Yuan, Minyan; Zhang, Min; Tang, Li; Wang, Pengjiao; Liu, Yujie; Xu, Changqian; Luo, Peng; Gao, Xiuli (Frontiers in Pharmacology, 2022)
Hyperlipidemia has become an important public health problem and endangers human health. This study was designed to investigate the anti-hyperlipidemia effects of Fermented Rosa Roxburghii Tratt juice (FRRT) in hyperlipidemic rats and to discover a new intervention strategy on hyperlipidemia. The studies showed that FRRT could significantly decrease the levels of body weight, total cholesterol (TC), triacylglycerol (TG), low-density lipoprotein cholesterol (LDL-c), and increased high-density lipoprotein cholesterol (HDL-c). We integrated the 16S rDNA sequencing and metabolomic profiling to evaluate the changes in the gut microbiota and metabolites. Marked changes in microbial composition were accompanied by significant changes in 56 feces metabolites. The results showed that FRRT could decrease the ratio of Firmicutes to Bacteroidetes. It also increased the abundance of some bacterial genera (Prevotella, Paraprevotellaceae_Prevotella, Ruminococcus, Oscillospira). Metabolomics analysis showed that bile acid metabolisms, amino acid metabolisms, and lipid metabolisms were greatly affected by FRRT. Correlation analyses suggest that the reductions in serum lipids by FRRT are associated with the gut microbial community and their associated metabolites (amino acid metabolites, bile acid metabolites, and lipid metabolites). Collectively, this study confirmed that FRRT could improve gut microbiota dysbiosis and metabolomic disorders and regulate dyslipidemia, which means FRRT could be used as a new dietary and therapeutic strategy to improve dyslipidemia. Our study also extended the understanding of the relationship between gut microbiota, metabolites, and lipid-lowering functions, and we need further studies to confirm this.